Invariant Submanifold of (4k, 2k) Structure Manifold - Lakhan Singh; Shailendra Kumar Gautam (International Journal of Mathematics And its Applications, 2016)
In this paper, we have studied various properties of a (4k, 2k) structure manifold and its invariant submanifold, where k is positive integer. Under two different assumptions, the nature of induced structure ψ, has also been discussed.